2000
DOI: 10.1215/03616878-25-3-527
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Time off Work after Childbirth

Abstract: Relatively little is known about the role that leave policies--family, parental, or maternity-leave policies--play in facilitating time off work after childbirth. Yet time off is a critical element of leave policies, as it facilitates the mother's recovery from childbirth and promotes maternal-infant attachment. Using data from Minnesota, the state with the highest rate of female labor force participation, we examine the extent to which policies, relative to personal, job, and workplace characteristics, determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 11 publications
0
23
0
1
Order By: Relevance
“…The unpaid nature of the FMLA appears to make it harder for parents to take longer periods of leave. In fact, the few studies conducted on this issue have shown that unpaid leave policies result in women taking short durations of leave (Hofferth and Curtin 2006;McGovern et al 2000). In this study, the total number of days of paid leave provided by employer policy predicted the number of leave days women took after childbirth.…”
Section: Limitationsmentioning
confidence: 76%
See 2 more Smart Citations
“…The unpaid nature of the FMLA appears to make it harder for parents to take longer periods of leave. In fact, the few studies conducted on this issue have shown that unpaid leave policies result in women taking short durations of leave (Hofferth and Curtin 2006;McGovern et al 2000). In this study, the total number of days of paid leave provided by employer policy predicted the number of leave days women took after childbirth.…”
Section: Limitationsmentioning
confidence: 76%
“…A statespecific study of a disproportionate random sample of 654 women obtained from the Minnesota Department of Health in 1991 and 1992 found that 75 percent of Minnesota mothers had returned to work at twelve weeks postpartum, and 95 percent had returned to work at six months postpartum (McGovern et al 1997). Among these Minnesota mothers the average duration of total time off after childbirth for women with paid leave (any combination of paid maternity, vacation, or sick leave) benefits was approximately 10.5 weeks, and for those without any paid leave benefits it was approximately 6.5 weeks (McGovern et al 2000). Moreover, the mothers lacking paid leave benefits were younger and poorer than their peers with paid leave benefits, suggesting their economic vulnerability to unpaid leave.…”
Section: United States Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, providing women with some form of monetary compensation during their time off work may encourage more women to take the leave that is provided. 49 …”
Section: Discussionmentioning
confidence: 99%
“…41 Almost 50% of working women take some period of paid, unpaid, or disability leave during pregnancy, while over 80% of these women take leave after the birth of a child. 4 Consistent with our findings, data from Sweden, a country with a generous parental benefits program (up to 60 days of compensation prior to delivery, up to a total of 450 days in association with childbirth), suggest that 43% of working women use additional sick leave during pregnancy, most commonly for symptoms of back pain.…”
Section: Discussionmentioning
confidence: 99%